Using an Ecomap as a Tool for Qualitative Data Collection in Organizations. Issue 2 (May 2016) - Bennett, Jo; Grant, Natalie S.
Abstract: An ecomap is a social work data collection tool that is used to gather data about a participant's environment. Derived from Bronfenbrenner's ecological system theory, the ecomap can be used in adult education and human resource development to record information of in‐and‐out‐of‐work and learning experiences and show how these interactions support or hurt an individual. Information about important interactions in an individual's life can help the staffs in organizations understand employees or adult learners in ways that may not surface with merely work or educational interactions. This first‐hand knowledge of an individual's strengths or weaknesses can help the staff learn how to individualize employee and adult learner development. This personal knowledge can be an important part of an employee's and adult learner's performance, and personal and professional growth.